Identifying and Describing Best Clinical Practices for Children and Adolescents With Complex Communication Needs: A Scoping Review of Healthcare‐Based Interventions. - Resina, Paula; Mezzatesta, Marcela; Elias, Neus; Aparici, Melina; Mairena, Maria A. (Journal of Intellectual Disability Research, 2025)
Background: Children with complex communication needs (CCN), particularly those with autism spectrum disorder (ASD), experience significant communication challenges. This scoping review analyses the existing literature on clinical interventions designed to enhance communication in these children. The aim was to describe which intervention models are being evaluated in studies, which treatments have shown positive effects and what the clinical profile of children and adolescents who benefit from these interventions is. Method: The scoping review was conducted following the methodology for scoping reviews and the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses Extension for Scoping Reviews (PRISMA‐ScR). Results: The search strategy identified 797 records; eight records met all eligibility criteria and were included for review. The review found that multimodal interventions combining augmentative and alternative communication (AAC), naturalistic strategies and parent training were the most effective in improving both expressive and receptive communication. Conclusions: Despite the limited existing research, studies suggest that multimodal interventions can effectively enhance communication in children with CCN. This review highlights significant gaps in the literature, including the scarcity of studies with appropriate methodological rigour and the lack of standardised protocols for CCN interventions. There is a critical need for evidence‐based guidelines, professional training and policy development to ensure equitable access to effective interventions.